Patterns of Drug-induced Mortality in Maine, 2015 Update - Sorg, Marcella; Greenwald, Margaret; Wren, Jamie (Maine Policy Review, 2016)
Drug addiction and drug-induced mortality have received a good deal of attention nationally and in Maine in recent years. The authors review overall trends in the patterns of drug overdoses that have continued for nearly two decades, including those involving opioid pharmaceuticals, and discuss the recent resurgence of the illicit drugs heroin and non-pharmaceutical fentanyl.
Keywords: Drug addiction; opioids; heroine; fentanyl; Maine